228k views
2 votes
Solve in step-by-step processes: (8² + (150 - 168 + 24) - 5²) ÷ (3 × 5 - 3 × 2²)

2 Answers

3 votes

Answer:


27

Step-by-step explanation:

To solve this, we must follow the PEMDAS rule:

Parenthesis

Exponents

Multiply

Divide

Add

Subtract

So lets start on the left equation:

Since parenthesis is first, we must do this:

(150 - 168 + 24)

168 + 24

==> 192

192 - 150

==> 42

So right now we have:

(
8^(2) + 42 -
5^(2)

Do the exponents now:


8^(2) = 64 and
5^(2) = 25

64 + 42 - 25

64 + 42

==> 106

106 - 25

==> 81

So now we have 81 for the left equation, now for the right:

(3 × 5 - 3 × 2²)

Exponents first:


2^(2) = 4

(3 × 5 - 3 × 4)

3 * 5

==> 15

3 * 4

==> 12

15 - 12

==> 3

So now we should be with:

81 divided by 3

81 ÷ 3

==> 27

User Liran H
by
5.8k points
5 votes
I’d do believe the answer is 15. I hope I’m right:)
User Kyrollos
by
4.8k points